Health migration policies and ethical controversies: the case of African nurses in the UK - Mendy, A (International Migration Institute, 2015)
The United Kingdom (UK) for the last few decades has been faced with a growing need for health personnel and has therefore attracted professionals, particularly overseas nurses. The country has been characterised by a historical migration policy favourable to the recruitment of foreign health staff. However, in the context of deep shortages and high level of diseases and health system weaknesses, international health professional recruitment from sub-Saharan Africa has created unprecedented ethical controversies, pushing the UK to the centre of discussions because of its liberal policies towards international recruitment that have been considered as aggressive. While the 'brain drain’ controversy is well known, less attention has been devoted to the specific international health migration controversy and the pivotal role of the UK in the diffusion of an ethical code of practice. Using mainly the perspective of the policy analysis of controversy (Roe 1994) and the analysis of discourses (de Haas 2008), this paper comes back respectively to the nature of the controversy and the pivotal role of the UK. It also analyses how the implementation of UK ethical policies – the Code of Practice, the banned countries recruitment list, and restrictive immigration policies – have been considered as inefficient and unethical in their contents and their targets.